Protótipo para medição de energia elétrica residencial utilizando plataforma arduino - Silva, Judson Praxedes da (Universidade Federal Rural do Semi-Árido, 2018)
Since residential electricity consumption increases every year, there is a need to encourage the consumer to take proactive measures to minimize the waste resulting from this increase. Based on this, the present work aims to develop a prototype capable of performing the measurement of electrical energy in a single-phase circuit. This will use as base the arduino platform for its development, as well as the creation of an algorithm that allows the interaction between hardware and software. Finally, measurements of electrical quantities (current, voltage, power) will be carried out in order to estimate the individual consumption of a device in real time, comparing the results obtained between different types of energy meters.
Monografia
Keywords: Consumo; Protótipo; Arduino; Medição de energia; Tempo real; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA